Identification of molecular markers for resistance to Fusarium head blight in wheat - Farooqi, Arifa (2018)
Fusarium head blight (FHB) is a devastating fungal disease of wheat and small grain cereals worldwide, causing yield losses, reducing grain quality, and leading to mycotoxin contamination of grain. Breeding for resistance to FHB by conventional selection is feasible, but the main challenge is to identify new genotypic variations and increase resistance by pyramiding multiple traits and quantitative trait loci (QTL). The aim of this work was to determine the physiological traits related to passive resistance and identify QTL conferring active resistance to the FHB. Double haploid (DH) wheat lines were ground inoculated in field experiments to enable passive disease traits to be expressed under natural rainfall and artificially misted conditions whilst ear inoculated glasshouse experiments were used to test if any of the assessed traits were associated with genetic resistance. Spikelet density was identified as a potential ear trait in the field contributing consistently to increased FHB progression. Flag leaf length and tiller number influencing pathogen dispersal and spread within the canopy were the most consistently significant traits, positively related to FHB development indicating a potential underlying genetic linkage which was not confirmed in subsequent QTL analysis. Instead these traits were associated with increased susceptibility and were negatively affecting any passive resistance mechanisms such as disease escape. To identify QTLs for canopy and ear traits, and resistance to FHB and Septoria tritici blotch (STB), a DH population of 107 lines was evaluated in two Fusarium and Microdochium ground inoculated, artificially misted and two Microdochium seed inoculated, non-misted experiments. A coinciding QTL for AUDPC and bleaching was found on chromosome 7D and a second QTL on 2B. An overlapping QTL for FHB lesions was detected on 5B and a second QTL on 4A conferring resistance to M. majus and fungal biomass accumulation in grain and in anthers. F .graminearum DNA in grain and anthers was conferred by a distinct QTL on 4B. QTLs for resistance to accumulation of deoxynivalenol (DON) and zearalenone (ZON) were detected on 5A and 6B, respectively. This study is the first to report the coexistence of resistance QTL for fungal biomass accumulation in grain and anthers and novel QTL for ZON in wheat. A QTLs for STB was found on chromosome 2A, for awns length on 5A. A QTL for flag leaf length on 3A and coincided QTLs for flag leaf length and flag leaf width on 7B failed to coincide with disease traits suggesting that the identified canopy traits were not genetically linked with disease but of rather epidemiological significance. The study identified separate QTLs conferring resistance to different Fusarium and Microdochium species indicating that resistance is distinctly regulated and likely to be species specific. To identify novel ear traits and determine the role of anthers and pollen in resistance to initial infection (Type I) or FHB susceptibility, ear inoculated glasshouse experiments using selected wheat genotypes and a point inoculated growth room experiment using fertile barley line (cv. Golden Promise) and cytoplasmic male sterile (CMS) lines (HvMS1 and HvDYT1) were conducted. The most consistent traits in glasshouse experiment were ear length, number of spikelets per ear and anther extrusion. Sugar concentrations in wheat anthers was quantified to observe the potential nutritional role played by different sugars for spore germination and infection by F. graminearium. Results from in vitro anther-fungal bioassays indicated that fungal spores utilize sucrose and fructose during germination and glucose for growth and infection. The role of anthers and pollen and possible biochemical substrate stimulating spore germination and fungal growth in wheat and barley in addition to Arabidopsis wild ecotypes (Columbia and Landsberg erecta) and mutants ABORTED MICROSPORES (AMS) producing non-viable pollen, MALE STERILITY1 (MS1) producing no pollen and MS35 non-dehiscing anther was investigated in a series of bioassays. CMS lines with infertile anthers were more resistant to FHB infection than wild type (WT). Spore germination was significantly reduced in the presence of wheat anthers containing no pollen while barley CMS line HvMS1 and HvDYT1 with sterile anthers also showed reduced spores germination. In Arabidopsis WT spore germination was significantly higher in the presence of fertile anthers compared to the mutants MS1 and MS35. Releasing MS35 pollen significantly increased spore germination. Reduction in spore germination was observed in all heat stressed replicates, irrespective of the anther and pollen presence or absence. These results indicate that the presence of fertile anthers and subsequent release of pollen are an important part of the infection pathway and of susceptibility to FHB while heat stress can destroy any substance in anthers and pollen stimulating Fusarium spores in-vitro. The current research findings show that FHB resistance type I (resistance to initial infection), type II (resistance to spread) and type III (resistance to mycotoxin accumulation) in wheat is conferred by a combination of active and passive resistance traits whereas active resistance is also associated with alleles determining the morphological, physiological and biochemical plant characteristics. Moreover, the expression of active and passive resistance is highly influenced by the environmental interactions, inoculum source, pathogen species and virulence under field conditions. Consequently, selection for desirable canopy and ear morphology traits conferring improved type I resistance in combination with cultivars with substantial levels of type II resistance can improve the overall FHB resistance in wheat.